Curriculum for endoscopic submucosal dissection training in Europe: European Society of Gastrointestinal Endoscopy (ESGE) Position Statement - Pimentel-Nunes, Pedro; Pioche, Mathieu; Albéniz, Eduardo; Berr, Frieder; Deprez, Pierre; Ebigbo, A.; Dewint, Pieter; Haji, Amyn; Panarese, Alba; Weusten, Bas L. A. M.; Dekker, Evelien; East, James E.; Sanders, David S.; Johnson, Gavin; Arvanitakis, Marianna; Ponchon, Thierry; Dinis-Ribeiro, Mário; Bisschops, Raf (Endoscopy, 2019)
There is a need for well-organized comprehensive strategies to achieve good training in ESD. In this context, the European Society of Gastrointestinal Endoscopy (ESGE) have developed a European core curriculum for ESD practice across Europe with the aim of high quality ESD training.Advanced endoscopy diagnostic practice is advised before initiating ESD training. Proficiency in endoscopic mucosal resection (EMR) and adverse event management is recommended before starting ESD trainingESGE discourages the starting of initial ESD training in humans. Practice on animal and/or ex vivo models is useful to gain the basic ESD skills. ESGE recommends performing at least 20 ESD procedures in these models before human practice, with the goal of at least eight en bloc complete resections in the last 10 training cases, with no perforation. ESGE recommends observation of experts performing ESD in tertiary referral centers. Performance of ESD in humans should start on carefully selected lesions, ideally small ( < 30 mm), located in the antrum or in the rectum for the first 20 procedures. Beginning human practice in the colon is not recommended. ESGE recommends that at least the first 10 human ESD procedures should be done under the supervision of an ESD-proficient endoscopist.Endoscopists performing ESD should be able to correctly estimate the probability of performing a curative resection based on the characteristics of the lesion and should know the benefit/risk relationship of ESD when compared with other therapeutic alternatives. Endoscopists performing ESD should know how to interpret the histopathology findings of the ESD specimen, namely the criteria for low risk resection (“curative”), local risk resection, and high risk resection (“non-curative”), as well as their implications. ESD should be performed only in a setting where early and delayed complications can be managed adequately, namely with the possibility of admitting patients to a ward, and access to appropriate emergency surgical teams for the organ being treated with ESD.